2016
DOI: 10.15761/cmi.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Initial outcomes from an autism treatment demonstration

Abstract: In a prior peer-reviewed published medical result, significant moderation of autistic behaviors was achieved using a single supplement, the phytochemical sulforaphane. Concomitantly there have been anecdotal case studies indicating the practical and useful application of bio-resonance devices to mitigate a variety of behaviors reflected across the autistic spectrum. In a demonstration application, we undertook to combine both of these promising approaches for a small group of autistic individuals. Consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Among 92 attributes which were determined as moderate to severe or severely influenced by their ASD, 80% showed positive effects and 39% showed significant improvement. No adverse events were reported in this study [120].…”
Section: Hormesis and Autismmentioning
confidence: 58%
See 1 more Smart Citation
“…Among 92 attributes which were determined as moderate to severe or severely influenced by their ASD, 80% showed positive effects and 39% showed significant improvement. No adverse events were reported in this study [120].…”
Section: Hormesis and Autismmentioning
confidence: 58%
“…The most frequent side effects of sulforaphane include the following: insomnia (17%), flatulence (15%) and constipation (13%) [119]. A 28-week follow-up study including only six patients was performed by Evans and Fuller (2016).. In this study, each patient received sulforaphane extracted from broccoli sprout and were evaluated by certain attributes associated with ASD symptoms.…”
Section: Hormesis and Autismmentioning
confidence: 99%
“…Its suitability as a possibly viable candidate has been previously documented [1]. The original trial used a purified sulforaphane extract exclusively provided for their trial.…”
Section: Supplementmentioning
confidence: 99%
“…It is a follow-up to a prior report [1] which described the beginning of this Study using a combination strategy which we will shortly but briefly review below. That Study by Evans and Fuller in turn was initiated and prompted by yet a prior clinical trial [2] providing a simple, safe, over-the-counter food supplement, which yielded significant positive outcomes after a 18-week period.…”
Section: Introductionmentioning
confidence: 97%
“…The hope for the SFN’s efficiency in autism was brought to light by the placebo-controlled double-blind randomized study of Singh et al [ 14 ] which included young men (aged 13–27; 29 SFN/15 placebo) who showed significant improvement in the Aberrant Behaviour Checklist (ABC), the SRS-2, and Clinical Global Impression (CGI-I) scores with improved social interaction, verbal communication, and a reduction in abnormal behaviour. Several other case reports and open-label studies have indicated the favourable effects of SFN [ 15 , 16 ]. Evans and Fuller [ 15 ] studied the extent of improvement in ASD patients taking SFN.…”
Section: Introductionmentioning
confidence: 99%